Analysis of processes and methods for expanding the protein base coking plant. Note 1. The problem of expanding the serum base coking plant - Kashirnaya , N.O.; Korenev , O.V.; Sorokin , E.L.; Starovoit , A.G.; Malyi , E.I.; Starovoit , M.A. (Theory and Practice of Metallurgy, 2024)
Purpose. To analyze postmodern methods that allow expanding the raw material base for coking for the effective use of the country's fossil natural resources. Methodology. Analysis of modern and postmodern methods and technologies related to the methodology of expanding the raw material base for coking. Results. Priority methods for expanding the raw material base for coking were analyzed. The classification of methods was determined and divided into mechanical methods, thermal methods, and specific methods that involve changing the properties of coal. Methods involving coal compaction were analyzed. Scientific Novelty. The critical analysis of both domestic and foreign sources regarding existing methods and techniques for expanding the raw material base of coking revealed insufficient study of the issue, which prevents the implementation of the proposed technologies. Practical Significance. The study of the issue of expanding the raw material base of coking allowed establishing the insufficiency of knowledge and scientific provisions about the structure of caking coal and its properties, which makes its effective use impossible.